The issue of attracting young personnel to the civil service - Dotsenko, Tetiana (Public Administration and Regional Development, 2021)
The article presents the results of the analysis of the issue of attracting young people to public service taking into account social attitudes and trends that prevail among modern youth. The author, based on thematic questionnaire and analysis of domestic and foreign researches of previous years, analyzed the list of basic indicators, which are crucial when young people choose their professional path. This list contains the following items: dominant motivational elements; main problems and shortcomings of public service; categories of prestige and attractiveness; focus on priority directions of work; value installations and determination of the most significant competences, considering the outlook of young people. It has been established, that a key element of the future viability of the Ukrainian civil service is to attract young and ambitious specialists with a modern view of state-building, rejection of outdated, rudimentary approaches to understanding the essence of public administration, an established European-oriented outlook, mobility, openness and political unbiasedness. On the other hand, we need to reform some elements of the modern civil service, which do not correspond to the outlook and behavioral characteristics of young people The main approaches to determining the levels of sympathy and antipathy to public service are indicated. The main stop-factors and disadvantages preventing the involvement of young people in the public sector are highlighted, the moral-value orientations characteristic of the majority of modern youth are modeled and understanding of the primary needs of young public employees is achieved, considering the general psychosocial and philosophical worldview model of society and state perception by young people. The author emphasizes the importance of optimizing the existing system of attracting personnel to the civil service based of a study of the social climate, the gradual increase of the prestige of public service and the creation of more opportunities for creative and professional realization of young people.